GAMBARAN PSIKOLOGIS INDIVIDU DENGAN KECENDERUNGAN KLEPTOMANIA - Prabowo, Bangkit Ary; Karyono, Karyono (Faculty of Psychology, Diponegoro University, 2014)
AbstractKleptomania is the inability to refrain from the urge to steal items and is done for reasons other than personal use or financial gain. Alternatively, some of the main characteristics of the disorder, which consist of recurring intrusion feelings, an inability to resist the urge to steal, and a release of pressure following the theft, suggest that kleptomania could be an obsessive-compulsive spectrum disorder. Persons diagnosed with kleptomania usually gain satisfaction after his stolen activity was done. This study is a qualitative-phenomenological study. Two men involved in the study; both subjects had been encountered an impulse disorder for years. The results showed that both subjects made plans before they stole things. They had an ego defense mechanism against kleptomania impulse that emerged when there are external and internal factors that weaken their wishes. Subject who has a good ego defense mechanism, have a strong will to recover; however, subject who has a weak ego defense mechanism will have a weak will to recover.